The influence of base glass thermal history and heat treatment on the ionic conductivity optimization in Li2O-Al2O3-TiO2-P2O5 glass-ceramics - Amirreza Fadaei; Pourya LotfiPoor; Omid Banapour Ghaffari; Bijan Eftekhari Yekta; Sara Ahmadi (Journal of Materials Research and Technology)
This study investigates the optimization of ionic conductivity in Li2O-Al2O3-TiO2-P2O5 (LATP) glass-ceramics, promising candidates for solid-state electrolytes in lithium-based energy storage systems. LATP glasses were synthesized via the melt-quenching process, employing both melt pressing and twin-roller casting techniques. The influence of the base glass's thermal history and subsequent heat-treatment at 750 °C, 850 °C, and 950 °C was examined with respect to phase formation, microstructure, and ionic conductivity. Differential thermal analysis (DTA) revealed glass transition temperatures of 670 °C and 660 °C, and crystallization temperatures of 695 °C and 692 °C for G1 and G2, respectively. X-ray diffraction (XRD) confirmed the formation of LiTi2(PO4)3 as the primary conductive phase, with AlPO4 as a secondary phase. The relative proportions of these phases, influenced by the glass structure and applied heat treatment, affected the final microstructure and ionic conductivity. Scanning electron microscopy (SEM) and energy-dispersive spectroscopy (EDS) showed that heat treatment at 850 °C improved microstructural homogeneity and grain connectivity, leading to enhanced ionic conductivity. Electrochemical impedance spectroscopy (EIS) demonstrated the highest ionic conductivity for samples treated at 850 °C, with values of 1.17 × 10−3 S/cm for G1-850 and 9.72 × 10−4 S/cm for G2-850. These improvements were attributed to an optimal balance between the LiTi2(PO4)3 and AlPO4 phases. However, higher heat-treatment temperatures led to excessive AlPO4 crystallization and microcrack formation, negatively impacting conductivity. The results underscore the critical importance of precise control over both the thermal history of the base glass and heat-treatment conditions in optimizing the phase composition and microstructural properties of LATP glass-ceramics.